Perceived Gender Inequality in Access to Education in Rural Area of Osun Central Senatorial District - IDRIS-IYEKOLO, Olushola (Ilorin Journal of Education, 2025)
The study examined Stakeholders' perceived impact of gender inequality in access to education in rural areas of Osun Central Senatorial District of which two specific research questions were raised. The study adopted a qualitative research design. The participants of the study include 2 teachers, 2 parents, 4 students, and 2 community leaders, making a total of 10 participants purposively selected from Ada Village, a rural area in Boripe, Osun Central Senatorial District which was the research setting. A semi-structured interview was conducted and thematic analysis was used to analyze the data. The findings reveal that stakeholders in Osun Central Senatorial District offer a multifaceted perspective on gender inequality in education. While traditional beliefs and economic limitations create significant barriers for girls, there seems to be a growing awareness of the importance of girls' education. In addition, the study demonstrated that cultural beliefs discourage girls from pursuing academic excellence. The study recommended that concerted efforts are needed at multiple levels. Community leaders, parents, teachers, and students must be engaged in dialogue and education to challenge and change entrenched beliefs that disadvantage girls.